Buy-It-Now prices in eBay Auctions - The Field in the Lab - Tim Grebe; Radosveta Ivanova-Stenzel; Sabine Kröger (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2010)
Electronic commerce has grown extraordinarily over the years, with online auctions being extremely successful forms of trade. Those auctions come in a variety of different formats, such as the Buy-It-Now auction format on eBay, that allows sellers to post prices at which buyers can purchase a good prior to the auction. Even though, buyer behavior is well studied in Buy-It-Now auctions, as to this point little is known about how sellers set Buy-It-Now prices. We investigate into this question by analyzing seller behavior in Buy-It-Now auctions. More precisely, we combine the use of a real online auction market (the eBay platform and eBay traders) with the techniques of lab experiments. We find a striking link between the information about agents provided by the eBay market institution and their behavior. Information about buyers is correlated with their deviation from true value bidding. Sellers respond strategically to this information when deciding on their Buy-It-Now prices. Thus, our results highlight potential economic consequences of information publicly available in (online) market institutions.
urn:nbn:de:bvb:19-epub-13260-3
Keywords: C72; C91; D44; D82; 330; electronic markets; experience; online auctions; BIN price; buyout; Auktion; Internet; Auktionstheorie; Preismanagement; Informationsverhalten; Feldforschung; Test